Familiarity with words modulates interhemispheric interactions in visual word recognition - Kim, Sangyub; Kim, Joonwoo; Nam, Kichun (Frontiers in Psychology, 2022)
Bilateral redundancy gain (BRG) indicates superior performance in bilaterally presented word recognition in the left and right visual field relative to word recognition given in either the left or the right visual field. The BRG may be modulated by participants’ subjective familiarity with words as previous studies found smaller regional activations in the brain as they become proficient. It can be assumed that visual recognition of words with high subjective familiarity indicates skilled performance in visual recognition. Thus, this study examined the subjective familiarity effect of visual words on the BRG during lateralized lexical decision performances. It showed that the significant BRG of response times was only observed in the most familiar word condition (F4 levels), on the other hand, accuracy results revealed the significant BRGs in all the subjective familiar conditions (F1, F2, F3, and F4 levels). These results suggest that the bilateral presentation of identical words with higher subjective familiarity facilitates the recognition led by cooperative interactions between cerebral hemispheres. Therefore, the subjective familiarity of visual words modulates the efficiency of hemispheric interactions in visual word recognition.